Spotted fever rickettsiae in wild-living rodents from south-western Poland - Gajda, Ewa; Hildebrand, Joanna; Sprong, Hein; Buńkowska-Gawlik, Katarzyna; Perec-Matysiak, Agnieszka; Coipan, Elena Claudia (Parasites & vectors, 2017)
Background Rickettsiae are obligate intracellular alpha-proteobacteria. They are transmitted via arthropod vectors, which transmit the bacteria between animals and occasionally to humans. So far, much research has been conducted to indicate reservoir hosts for these microorganisms, but our knowledge is still non-exhaustive. Therefore, this survey was undertaken to investigate the presence of Rickettsia spp. in wild-living small rodents from south-western Poland. Results In total, 337 samples (193 from spleen and 144 from blood) obtained from 193 wild-living rodents: Apodemus agrarius , Apodemus flavicollis , and Myodes glareolus were tested by qPCR for Rickettsia spp. based on a fragment of gltA gene. The prevalence of infection was 17.6% (34/193). Subsequently, the positive samples were analysed by conventional PCR targeting the gltA gene fragment. The genus Rickettsia was confirmed by sequence analysis in four samples from the blood. In two blood samples from A. agrarius , the identified pathogen was Rickettsia helvetica . The Rickettsia obtained from A. flavicollis was assigned to Rickettsia felis -like organisms group. One isolate from A. agrarius could be determined only to the genus level. Conclusions This study shows the presence of Rickettsia DNA in tissues of wild-living rodents, suggesting some potential role of these animals in temporarily maintaining and spreading the bacteria in enzootic cycles.